2007
DOI: 10.1111/j.1365-2656.2007.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction diversity within quantified insect food webs in restored and adjacent intensively managed meadows

Abstract: Summary 1.We studied the community and food-web structure of trap-nesting insects in restored meadows and at increasing distances within intensively managed grassland at 13 sites in Switzerland to test if declining species diversity correlates with declining interaction diversity and changes in food-web structure. 2. We analysed 49 quantitative food webs consisting of a total of 1382 trophic interactions involving 39 host/prey insect species and 14 parasitoid/predator insect species. Species richness and abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
167
6
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 56 publications
12
167
6
2
Order By: Relevance
“…However, the variation in strength of the effect indicates that, although diversity may act in a similar way in different years, other drivers of herbivore abundance (such as climate or dispersal) may frequently mask the effects of plant diversity. In contrast, and in line with the Enemies Hypothesis (Root, 1973) and a range of more recent studies (Albrecht, Duelli, Schmid, & Muller, 2007; Bianchi et al., 2006; Haddad et al., 2009; Vanbergen, Hails, Watt, & Jones, 2006), parasitoid abundance increased with plant diversity. We found that both plant species richness and functional group richness were important components of diversity that affected the abundance of higher trophic levels.…”
Section: Discussionsupporting
confidence: 88%
“…However, the variation in strength of the effect indicates that, although diversity may act in a similar way in different years, other drivers of herbivore abundance (such as climate or dispersal) may frequently mask the effects of plant diversity. In contrast, and in line with the Enemies Hypothesis (Root, 1973) and a range of more recent studies (Albrecht, Duelli, Schmid, & Muller, 2007; Bianchi et al., 2006; Haddad et al., 2009; Vanbergen, Hails, Watt, & Jones, 2006), parasitoid abundance increased with plant diversity. We found that both plant species richness and functional group richness were important components of diversity that affected the abundance of higher trophic levels.…”
Section: Discussionsupporting
confidence: 88%
“…Fragmentation should therefore have increasingly negative effects on more specialised parasitoids, and several empirical studies support this conclusion (moth parasitoids: Elzinga et al, 2007;aphid parasitoids: Rand and Tscharntke, 2007;leafminer parasitoids: Cagnolo et al, 2009; parasitoids of cavity-nesting bees and wasps: Holzschuh et al, 2010). These findings suggest that the effects of fragmentation on parasitoids will largely be mediated by altered host distributions, which are often coupled to plant densities (for herbivorous hosts) at the patch scale (Albrecht et al, 2007;Amarasekare, 2000;Cronin et al, 2004;Holzschuh et al, 2010;Kruess, 2003;Schnitzler et al, 2011;Vanbergen et al, 2007).…”
Section: Antagonistic Host-parasitoid Interactionsmentioning
confidence: 67%
“…Coral reef photos are used by kind permission of José Eduardo Silva, Stephen Leahy, Nick Graham and James Acker (respective photo credits, from top to bottom). diversity of species (Albrecht et al, 2007). This suggests a strong impact of habitat fragmentation on trophic networks and that interaction diversity might decline more rapidly than species diversity in fragmented systems.…”
Section: Antagonistic Host-parasitoid Networkmentioning
confidence: 98%
See 2 more Smart Citations